2014
DOI: 10.3168/jds.2013-7166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed additives on rumen and blood profiles during a starch and fructose challenge

Abstract: We evaluated the effect of feed additives on the risk of ruminal acidosis in Holstein heifers (n = 40) fed starch and fructose in a challenge study. Heifers were randomly allocated to feed additive groups (n = 8 heifers/group): (1) control (no additives); (2) virginiamycin (VM); (3) monensin + tylosin (MT); (4) monensin + live yeast (MLY); and (5) sodium bicarbonate + magnesium oxide (BUF). Heifers were fed 2.5% of body weight (BW) dry matter intake (DMI) per day of a total mixed ration (62:38 forage:concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…Plasma ceruloplasmin concentrations observed in this case study were within the range reported in heifers (Golder et al 2014). Ceruloplasmin is a serum ferroxidase that contains greater than 95% of the copper found in plasma (Hussein et al 2012) and is involved in cellular pro-oxidant and antioxidant processes (Ehrenwald & Fox 1996).…”
mentioning
confidence: 57%
“…Plasma ceruloplasmin concentrations observed in this case study were within the range reported in heifers (Golder et al 2014). Ceruloplasmin is a serum ferroxidase that contains greater than 95% of the copper found in plasma (Hussein et al 2012) and is involved in cellular pro-oxidant and antioxidant processes (Ehrenwald & Fox 1996).…”
mentioning
confidence: 57%
“…Another mechanism through which replacing starch with sugars may enhance rumen health and nutrient utilisation, is that this stimulates butyrate production, and, thereby, the energy supply to and functionality of the rumen epithelium (Dionissopoulos et al, 2013;Malhi et al, 2013). Golder et al (2014b and2014c) also observed that sugars differ in their effect on reticulo-rumen function, including the production of lactic acid.…”
Section: Diet and Digesta Composition And Gastrointestinal Healthmentioning
confidence: 99%
“…Sensible approaches to controlling the risk include testing for quality, rumen degradability and/or risk of acidosis (a near IR reflectance test has been developed for this purpose); establishing a regular supply from a consistent source; and careful and consistent processing of grain. Use of by-products of human food production including flour and maize manufacturing processes and distilling wastes and fats to maintain the energy density of the diet and to control starch and sugar intakes are strategies employed to reduce the risk of acidosis and potentially increase the profitability of production (Lean et al, 2013;Golder et al, 2014b and2014c).…”
Section: Diet and Digesta Composition And Gastrointestinal Healthmentioning
confidence: 99%
“…Rumen modifiers such as monensin, virginiamycin, tylosin, and lasalocid have been evaluated for their ability to control the risk of acidosis (RAGFAR, 2007). Although evidence suggests that various rumen modifiers may provide some control of acidosis risk (Golder et al, 2014) when cows are fed high levels of concentrates (14 and 16 kg of DM; Auldist et al, 2013a) or when substantial ruminal concentrations of lactic acid (>20 mmol/L) were present (Golder et al, 2014), the risk of acidosis was not controlled by the rumen modifiers used. The large variability between animals in response to rumen modifiers (Golder et al, 2014) supports the need for a biomarker indicative of poor rumen function to ensure all animals are managed optimally.…”
Section: Potential For Individualized Feeding To Mitigate the Risk Ofmentioning
confidence: 99%